Problems Related to Social Media Use in Finnish Adolescents: Gender Differences and Correlates - Terhi Mustonen; Kirsimarja Raitasalo; Sari Castrén (International Journal of Environmental Research and Public Health, 2026)
Background: Problematic social media use among adolescents has emerged as a growing public health concern. This study examined gender differences in problems related to social media use and their behavioural, psychosocial, family-related, and school-related correlates among Finnish adolescents. Methods: In this cross-sectional study, binary logistic regression analyses were conducted using data from the Finnish sample of the 2024 European School Survey Project on Alcohol and Other Drugs (ESPAD), including 3293 adolescents aged 15–16 years. Results: Overall, 45% of girls and 30% of boys were classified as having problems related to social media use. Significant gender interactions were observed in the associations of gaming-related problems and perceived family socioeconomic status with problems related to social media use. Gaming-related problems were the strongest correlate, with a substantially stronger association among boys. Elevated psychological distress was associated with a higher likelihood of problems related to social media use, particularly among girls, whereas higher parental monitoring was associated with a lower likelihood only among girls. Truancy and plans for general upper secondary school were both associated with a higher likelihood of problems related to social media use among girls and boys. Conclusions: The findings suggest that problems related to social media use are closely linked to adolescent well-being and behaviour. Prevention and intervention efforts may therefore benefit from addressing problematic social media use as part of adolescent mental health and digital well-being strategies, combining universal approaches with targeted support for adolescents experiencing problematic patterns of digital media use.